Sumbing Median (Midline Cleft) - Ishandono Dachlan; A. Yuda Handaya; Sagiran Sagiran (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2005)
Midline Cleft is a midline deformity of the upper lip and nose (Tessier Clasification of Cleft Number 0 ). It is rare and often accompanied by disorder of the central nervous system. Head CT Scan with a better architecture of the brain has a better prognosis and those with poor differentiation of brain die during infancy. The treatment of choice is surgical procedure to correct the deformity by Z-plasty or its modification. The aim of this stydy is to report the management of a midline cleftTwo Cases has been reported, The first case was a 13 year-old girl suffering from a midline upper lip cleft, she visited to Sardjito Hospital because of a cosmetic problem, and she had a good achievements at School, The head CT Scan showed a normal brain architecture. She had undergone an upper lip modification Z- Plasty. The second case was a 2 day-old male baby within absence of collumella and prolabial segment of lip (false median cleft), absence of the premaxilla skeletal and he suffers multiple anomalies, the head CT scan showed poor differentiation of brain.Result of this study showed that the one case has showed a good result after upper lip modification of Z-Plasty, the second case died before treated any surgical operation. It can concluded that midline cleft should be treated with observing other problems or anomalies especially of the brain structure and followed with delicate method of surgical procedure.Sumbing median adalah kelainan median pada bibir atas dan hidung (Klasifikasi Tessier, Cleft Nomor 0). Sumbing median adalah kelainan yang jarang terjadi dan biasanya disertai dengan gangguan sistem syaraf pusat. CT Scan kepala yang menunjukkan struktur otak baik mempunyai prognosis lebih baik, Gambaran struktur otak yang jelek biasanya meninggal pada awal kehidupan atau masa pertumbuhan. Terapi pilihan biasanya berupa prosedur pembedahan untuk mengoreksi kelainan, dengan teknik Z-plasty atau modifikasinya. Tujuan dari kajian ini adalah untuk melaporkan penatalaksanaan dua buah kasus sumbing median.Delaporkan dua kasus sumbing median, kasus pertama wanita usia 13 tahun menderita sumbing pada pertengahan bibir atas, pasien datang ke Rumah sakit Sardjito dengan keluhan kosmetik, pasien mempunyai prestasi yang baik di sekolah. CT Scan kepala menunjukan gambaran otak normal. Pasien dilakukan operasi Z- Plasty pada bibir atas. Kasus ke dua,pasien laki-laki usia 2 hari dengan tidak adanya collumella danprolabial, serta tidak adanya tulang premaxilla, pasien menderita anomali multipel, CT Scan kepala menunjukan gambaran otak yang tidak sempurna.Kasus pertama menunjukan hasil yang baik setelah dilakukan operasi Z-Plasty, kasus kedua meninggal sebelum dilakukan tindakan bedah. Oleh karena itu dapat disimpulkan bahwa penatalaksanaan sumbing median harus memperhatikan anomali lain terutama struktur otak dan perlu mempertimbangkan teknik operasi yang tepat untuk mendapatkan hasil yang baik.